2017
DOI: 10.1002/ajim.22790
|View full text |Cite
|
Sign up to set email alerts
|

DNA variants and organophosphate neurotoxicity among emerging farmers in the Western Cape of South Africa

Abstract: BackgroundPrevious epidemiological studies investigating modification of organophosphate (OP) neurotoxicity by xenobiotic metabolizing enzymes (XMEs) polymorphisms have produced inconsistent results.MethodsA cross‐sectional study of 301 emerging farmers was conducted. Neurotoxicity testing included forward and backward recall, digit span, and vibration sensitivity testing. Questionnaire data included demography, potential confounders, and work history of pesticide exposures. Genomic DNA was analyzed from study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Of the 104 total journal articles reviewed here, 57 investigated the relationship between pesticide exposures in agricultural work and known areas of the brain. Of the 57 articles concerning pesticide exposure, 20 considered all pesticides without mentioning subcategories, nine focused on insecticides [ 96 , 98 , 100 , 104 , 105 , 109 , 113 , 116 , 149 ], six focused on organophosphate pesticides [ 92 , 93 , 95 , 103 , 112 , 117 , 123 , 139 ], three focused on herbicides [ 111 , 133 , 136 ], and the rest focused on either a specific pesticide (e.g., cypermethrin) [ 134 ], or a type of pesticide defined by the type of agriculture where it’s used (e.g., pesticides used on vineyards) [ 137 ]. Because some reviews exist on certain specific types of pesticides, we included all chemicals used to eliminate insects, fungi, and unwanted plants in our definition of pesticides and do not separate them into subgroups below [ 24 , 27 , 42 , 150 , 151 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 104 total journal articles reviewed here, 57 investigated the relationship between pesticide exposures in agricultural work and known areas of the brain. Of the 57 articles concerning pesticide exposure, 20 considered all pesticides without mentioning subcategories, nine focused on insecticides [ 96 , 98 , 100 , 104 , 105 , 109 , 113 , 116 , 149 ], six focused on organophosphate pesticides [ 92 , 93 , 95 , 103 , 112 , 117 , 123 , 139 ], three focused on herbicides [ 111 , 133 , 136 ], and the rest focused on either a specific pesticide (e.g., cypermethrin) [ 134 ], or a type of pesticide defined by the type of agriculture where it’s used (e.g., pesticides used on vineyards) [ 137 ]. Because some reviews exist on certain specific types of pesticides, we included all chemicals used to eliminate insects, fungi, and unwanted plants in our definition of pesticides and do not separate them into subgroups below [ 24 , 27 , 42 , 150 , 151 ].…”
Section: Resultsmentioning
confidence: 99%
“…The authors of this study suggested that lack of association could be related to the small number of participants using paraquat pesticides and the historically low levels of pesticides being used in Finland where the study was conducted [ 83 ]. When considering pesticide exposure, multiple studies pointed to an important genetic influence; specifically, some individuals are more likely to experience Parkinsonism due to genetic differences in genes that encode dopamine receptors [ 116 , 117 , 121 ]. There appear to be important sex-based differences with men at greater risk than women for Parkinson’s disease after occupational exposure to pesticides [ 120 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies document the correlation between high-level OP exposure and neurological or neuropsychological impairments (Naughton and Terry 2018;Glass et al 2018). Neurological and psychological effects of OPs can be associated with either acute or chronic exposure and may include motor dysfunction and extrapyramidal symptoms, psychosis, anxiety, depression, as well as defects in attention, memory, problem-solving, cognition, and delayed polyneuropathy (Pereira et al 2014;Naughton and Terry 2018).…”
Section: Neurotoxicitymentioning
confidence: 99%
“…Aqiel Dalvie discussed lessons from the fields with respect to the implications of interventions. In his studies, he found that sprayers, non-sprayers, farm residents, and neighboring nonfarm residents, including vulnerable groups, were at risk for exposure and possible long-term adverse health effects [ 12 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. Proximity is a relevant factor for aerial exposure, but other sources of exposure are also relevant such as drinking water from an open water source, eating crops from the agricultural areas and gardens, or obsolete stocks.…”
Section: Resultsmentioning
confidence: 99%